YouTube Sentiment Reveals Public Perception of Lapindo Mud Tourism: Analisis Sentimen YouTube Mengungkap Persepsi Publik terhadap Pariwisata Lumpur Lapindo - Nahariqi, Muhammad Iqbal; Findawati, Yulian; Kautsar, Irwan Alnanrus; Rosid, Mochamad Alfan (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Social media platforms provide extensive public opinion data that can be utilized to understand perceptions of tourism destinations. Specific Background: YouTube comments related to Lapindo Mud tourism contain diverse viewpoints reflecting visitors’ experiences and societal responses to the site. Knowledge Gap: Limited studies analyze public sentiment toward disaster-related tourism destinations using machine learning–based text mining approaches. Aims: This study classifies YouTube user comments to identify sentiment patterns regarding Lapindo Mud tourism using TF-IDF weighting and the K-Nearest Neighbor (K-NN) algorithm. Results: From 520 labeled comments, the model achieved 78% accuracy, with higher precision and recall in identifying negative sentiment than positive sentiment. Novelty: The study integrates sentiment analysis, expert-based labeling, and tourism perception assessment to examine how digital discourse represents a disaster-turned-tourism site. Implications: Findings provide insights for tourism stakeholders and local authorities to understand public perception and inform strategies for managing the image and communication of Lapindo Mud as a tourism destination.